2020
DOI: 10.2323/jgam.2019.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Induction of mutation in <i>Monascus purpureus</i> isolated from Thai fermented food to develop low citrinin-producing strain for application in the red koji industry

Abstract: Induction of mutation in Monascus purpureus isolated from Thai fermented food to develop low citrinin-producing strain for application in the red koji industry

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…[ 137,138 ] According to the document of European Union (Commission Regulation [EU] No 212/2014 of March 6, 2014), the food standards for MPs require the CIT titer to be less than or equal to 2 mg kg −1 . To enhance MPs production while minimizing CIT content, current research focuses on screening strains, [ 139,140 ] optimizing fermentation conditions, [ 141,142 ] and incorporating exogenous substances. [ 111,143 ] For example, with strain screening strategy, the MPs yield is almost two folds as compared to the parental strain and the CIT is almost non‐existent.…”
Section: Citrinin Removal and Metabolite Biosynthesis In Monascusmentioning
confidence: 99%
“…[ 137,138 ] According to the document of European Union (Commission Regulation [EU] No 212/2014 of March 6, 2014), the food standards for MPs require the CIT titer to be less than or equal to 2 mg kg −1 . To enhance MPs production while minimizing CIT content, current research focuses on screening strains, [ 139,140 ] optimizing fermentation conditions, [ 141,142 ] and incorporating exogenous substances. [ 111,143 ] For example, with strain screening strategy, the MPs yield is almost two folds as compared to the parental strain and the CIT is almost non‐existent.…”
Section: Citrinin Removal and Metabolite Biosynthesis In Monascusmentioning
confidence: 99%
“…Taking a further step, Ketkaeo et al . revealed that the combination of UV irradiation along with N ‐methyl‐ N ′‐nitro‐ N ‐nitrosoguanidine treatment can completely eliminate citrinin production 55 …”
Section: Approaches To Reducing the Citrinin Productionmentioning
confidence: 99%
“…54 Taking a further step, Ketkaeo et al revealed that the combination of UV irradiation along with N-methyl-N′-nitro-Nnitrosoguanidine treatment can completely eliminate citrinin production. 55 Of note, when it comes to genetic engineering conducted on citrinin reduction, the knockout gene should be selected carefully. For example, Chen et al found that the deletion of Ash2, encoding histone methyltransferase, obviously inhibited citrinin formation but also undesirably hindered pigment production.…”
Section: Approaches To Reducing the Citrinin Productionmentioning
confidence: 99%